Clinical Identification of Hypovitaminosis D among Elderly Attending Primary Care Centre in Saudi Arabia - Abdullah M. Alzahrani; Leena S. Emam; Maryam S. Alsharif; Alqassem Y. Hakami; Syed Sameer Aga (Biochemistry Research International)
Background. A large proportion of elderly people suffer from hypovitaminosis D, and depending on the severity of the condition, they develop complications that are detrimental to their health. Objective. To determine the consistency between the results of the vitamin D level in the blood compared to the result with the score of a simple questionnaire (Physician Vitamin D Status Predictor - VDSP) for elderly patients. Subjects and methods. This is a cross-sectional study conducted during the period between October 2018 and November 2019 in 3 primary health care centres (PHCCs) in Jeddah, Saudi Arabia. The subjects for this study were patients aged 60 or older. Data were collected in two phases: a questionnaire approach as the first phase, while the second phase involved blood testing for vitamin D levels. The validated questionnaire used in this study was the Physician`s Vitamin D Status Predictor (VDSP). Results. The study included 335 participants who ranged between 60 and 107 years old with a mean age of 68.2 years and standard deviation (SD) of 7.3 years. Females represented 66.9% of the total participants. The prevalence of vitamin D deficiency was 60.8%; among them, 7.2% were categorized as severe deficiency, whereas the prevalence of vitamin D insufficiency was 29.9%. The outcomes of VDSP survey were not directly associated with serum 25(OH)D levels in elderly people, except for the number of medications. In addition, vitamin D supplementation was associated with serum 25(OH)D levels among those patients. Conclusion. Vitamin D supplementation was significantly associated with serum 25(OH)D levels. Moreover, this study showed a significant association between serum 25(OH)D levels and the number of medications taken by the participants.